A comparison of oral controlled-release morphine and oxycodone with transdermal formulations of buprenorphine and fentanyl in the treatment of severe pain in cancer patients - Nosek, Krzysztof (Drug Des Devel Ther, 2017)
AIM OF THE STUDY: To compare analgesia and adverse effects during oral morphine and oxycodone and transdermal fentanyl and buprenorphine administration in cancer patients with pain. PATIENTS AND METHODS: Cancer patients treated at home and in outpatient clinics with severe pain (numerical rating scale score 6–10) fail to respond to non-opioids and/or weak opioids. All patients were randomized to either morphine, oxycodone, fentanyl or buprenorphine and divided into subgroups with predominant neuropathic and nociceptive pain component. Doses of opioids were titrated to satisfactory analgesia and acceptable adverse effects intensity. Patients were assessed at baseline and followed for 28 days. In all patient groups, immediate-release oral morphine was the rescue analgesic and lactulose 10 mL twice daily was the prophylaxis of constipation; no antiemetics were used as prophylaxis. RESULTS: A total of 62 patients participated and 53 patients completed the study. Good analgesia was obtained for all 4 opioids, for both nociceptive and neuropathic pain. The use of co-analgesics was greater in patients with neuropathic pain. Morphine treatment was associated with less negative impact of pain on ability to walk, work and activity (trend) according to Brief Pain Inventory-Short Form scores and less consumption of rescue morphine. The most common adverse effects included nausea and drowsiness, which increased at the beginning of the treatment and gradually decreased over the days to come. Appetite, well-being, anxiety, depression, and fatigue improved. There was no constipation (the Bowel Function Index scores were within normal range) during the treatment with all opioids. No changes were seen for constipation, vomiting and dyspnea. CONCLUSION: All opioids were effective and well-tolerated. Morphine was the most effective in the improvement in some of the Brief Pain Inventory-Short Form items regarding negative impact of pain on patients’ daily activities. Prophylaxis of constipation was effective; antiemetics may be considered for nausea prevention.